Renal arteries: optimization of three-dimensional gadolinium-enhanced MR angiography with bolus-timing-independent fast multiphase acquisition in a single breath hold - Schönberg, Stefan; Bock, Michael; Knopp, Michael V.; Essig, Marco; Hawighorst, Hans; Kallinowski, Friedrich; Kaick, Gerhard van (Radiology, 1999)
PURPOSE: To compare two different three-dimensional (3D) gadolinium-enhanced magnetic resonance (MR) angiographic techniques. MATERIALS AND METHODS: In 26 patients suspected of having renal artery stenosis, results with fast multiphase 3D MR angiography were compared to those with standard 3D MR angiography in 37 patients.
Gesehen am 18.02.2021